The Interplay of Teacher Workload, Student Achievement, and Buddhist Philosophy in Shaping Educational and Business Connections within Science and Technology - Erwin Ernestus Kadar Slamet; Selvi Agustina (Journal of Management and Social Sciences, 2023)
This qualitative research aims to investigate the intricate interplay between teacher workload, student achievement, and Buddhist philosophy in shaping connections between education and business realms in science and technology fields. Employing a phenomenological research model, the study will utilize purposive sampling to select participants from educational and business sectors. Data analysis will be conducted through thematic analysis, unraveling the nuanced relationships among the variables. The study anticipates revealing how Buddhist philosophical principles influence pedagogical practices, thereby impacting student outcomes and fostering collaborative ventures between academia and industry. Results are expected to provide insights into holistic educational approaches and the potential for synergy between spiritual values and technological advancements.